ACR Appropriateness Criteria® Locoregional therapy for resectable oropharyngeal squamous cell carcinomas. Issue 9 (22nd June 2016) - Beitler, Jonathan J.; Quon, Harry; Jones, Christopher U.; Salama, Joseph K.; Busse, Paul M.; Cooper, Jay S.; Koyfman, Shlomo A.; Ridge, John A.; Saba, Nabil F.; Siddiqui, Farzan; Smith, Richard V.; Worden, Francis; et al.
Abstract: Background: There are no level I studies to guide treatment for resectable oropharyngeal squamous cell carcinoma (SCC). Treatment toxicities influence management recommendations. Ongoing investigations are examining deintensified treatments for human papillomavirus (HPV)‐associated oropharyngeal SCC. Methods: The Appropriateness Criteria panel, using modified Delphi methodology, produced a literature summary, an assessment of treatment recommendations, and cases to illustrate their use. Results: A multidisciplinary team produces optimum results. Based on HPV status, smoking history, and staging, patients are divided into groups at low, intermediate, and high‐risk of death. In the future, treatment recommendations may be influenced by HPV status, which has changed the epidemiology of oropharyngeal SCC. Conclusion: T1 to T2N0M0 resectable oropharyngeal SCC can be treated with surgery or radiation without chemotherapy. Patients with T1‐2N1‐2aM0 disease can receive radiation, chemoradiation, or transoral surgery with neck dissection and appropriate adjuvant therapy. Patients with T1‐2N2b‐3M0 disease should receive chemoradiation or transoral surgery with neck dissection and appropriate adjuvant therapy. Concurrent chemoradiation is preferred for T3 to T4 disease. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1299–1309, 2016